2018
DOI: 10.1155/2018/5164314
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Inflammatory Effects of Berberine Hydrochloride in an LPS‐Induced Murine Model of Mastitis

Abstract: Berberine hydrochloride is an isoquinoline type alkaloid extracted from Berberidaceae, Rutaceae, and other plants. Previous reports have shown that berberine hydrochloride has anti-inflammatory properties. However, the underlying molecular mechanisms remain unclear. In this study, a lipopolysaccharide- (LPS-) induced murine model of mastitis was established to explore the anti-inflammatory action of berberine hydrochloride. Sixty mice that had been lactating for 5–7 days were randomly divided into six groups, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 24 publications
1
19
0
1
Order By: Relevance
“…4), which suggest that BBR has anti-inflammatory effects mainly through NF-κB deactivation in LPS-exposed mIMCD-3 cells. Some previous researches have reported that BBR inhibits inflammatory mediators and NF-κB signaling in various different disease models (19,(63)(64)(65)(66)(67). However, there is no report that BBR could have anti-inflammatory and protective effects in lPS-exposed inner medullary collecting duct (iMcd) cells.…”
Section: Discussionmentioning
confidence: 99%
“…4), which suggest that BBR has anti-inflammatory effects mainly through NF-κB deactivation in LPS-exposed mIMCD-3 cells. Some previous researches have reported that BBR inhibits inflammatory mediators and NF-κB signaling in various different disease models (19,(63)(64)(65)(66)(67). However, there is no report that BBR could have anti-inflammatory and protective effects in lPS-exposed inner medullary collecting duct (iMcd) cells.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the major compounds of CBT were identified by HPLC, and it was confirmed that it contains crocin (28.671 mg/g), berberine hydrochloride (6.255 mg/g), and glycyrrhizic acid (6.249 mg/g). Previous studies have reported these compounds have anti-inflammatory and anti-oxidant effects (Fagot et al, 2018;Wang et al, 2018).…”
mentioning
confidence: 99%
“…BBRH has been widely used as a therapeutic agent for infections and heart failure (Fu et al 2015) due to its antiviral, antibacterial, and blood pressure-reducing activities. It was previously demonstrated that BBRH could be effectively used against LPS-triggered endometritis in mice (Wang et al 2018). Neutrophil infiltration and MPO function was repressed by BBRH via NFκB stimulation (Shao et al 2015).…”
Section: Discussionmentioning
confidence: 98%